Pemanfaatan Biofilter untuk Mengurangi Pemakaian Bahan Kimia dalam Proses Pengolahan Air Estuary - Ketut Gede Suryawan; I Gede Mahardika Mahardika; I Wayan Budiarsa Suyasa (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2017)
The process to supply the drinking water will also be expensive due to the decreasing quality of water it self. Some chemical substances are needed in high quantity to produce healthy water from Badung River, such as chlorine and aluminum sulphat (Al SO4). This is because the polutants of water in Badung River is really high. To decrease the use of the amount of chemical subtances and to avoid the side effect of chlorine on water which is highly organic, so this research was done through the use of biofilter. This biofilter is like bee-hive which is made from plastic. This micro-organism would scatter the organic substance and ammonia. In this case, iron (Fe) and Manganese (Mn) would be oxydized by the air and water from the blower. On the next step, the measurement of the content in each organic substance, iron, manganese, nitrate, nitrite, ammonia was done on the streaming water and the water that was out from biofilter reactor. In every parameter, the sampel was taken periodically from 1 to 6 hours hydrolic-setting time. The testing of using aluminum sulphate and the needs of chlorine was done in every 1 to 6 hours hydrolic-setting time. The result of the research told us that for 6 hours hydrolic- setting time could decrease 38.78% the organic substance, iron ( Fe) 41.93%, manganese (Mn) 55.32%, ammonia 75.40%, nitrite 55.32%, but nitrate increased up to 53.85%. The increase of nitrate is still tolerable based on the law of governor (Pergub) Bali No. 8 year 2007. The use of chemical substance, in this case aluminum sulphat could be decreased up to 10 ppm and chlorine (gas) could also be decreased until 10 ppm.